2020
DOI: 10.1016/j.xpro.2020.100191
|View full text |Cite
|
Sign up to set email alerts
|

Protocol for Imaging and Analysis of Mouse Tumor Models with CUBIC Tissue Clearing

Abstract: Summary Tissue-clearing technologies have developed rapidly in the past decade, especially for use in neuroscience research. We previously reported that CUBIC, which is one tissue-clearing method, is useful for applications in cancer research. CUBIC cancer analysis can be used to detect cancer metastasis with single-cell resolution at whole mouse body/organ level. This approach can also analyze the tumor characteristics with high-quality 3D images. Here, we describe a detailed CUBIC cancer protocol … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 4 publications
0
12
0
Order By: Relevance
“…In our current tissue-clearing method with CUBIC reagents (CUBIC-L and CUBIC-R (N)), a perfusion step with PBS and PFA is needed to reduce autofluorescence signals from red blood cells. 18,27,28 Tainaka et al showed that CUBIC-L reagent not only has the ability of delipidation but also a high ability to decolorize tissues, especially by removing heme. 7 Here, we showed that primary tumors in the orthotopic model with 4T1-Fucci cells were also visualized with 3D images using the CUBIC reagent (Figure 3A).…”
Section: Discussionmentioning
confidence: 99%
“…In our current tissue-clearing method with CUBIC reagents (CUBIC-L and CUBIC-R (N)), a perfusion step with PBS and PFA is needed to reduce autofluorescence signals from red blood cells. 18,27,28 Tainaka et al showed that CUBIC-L reagent not only has the ability of delipidation but also a high ability to decolorize tissues, especially by removing heme. 7 Here, we showed that primary tumors in the orthotopic model with 4T1-Fucci cells were also visualized with 3D images using the CUBIC reagent (Figure 3A).…”
Section: Discussionmentioning
confidence: 99%
“…Tissue clearing was performed using the CUBIC regents 10 , 12 , 13 . Mice were sacrificed and perfused with 20–30 ml phosphate buffered saline (PBS) and 20–30 ml 4% PFA (Wako) in PBS.…”
Section: Methodsmentioning
confidence: 99%
“…For the detection of metastatic tumors in mouse models, the whole brain and lung were cleared by CUBIC‐L/R as previously described. 21 , 22 The brains of the mice were co‐stained with anti‐α‐smooth muscle actin (α‐SMA) antibody, as indicated in Table S1 . Images were acquired with a light‐sheet fluorescence microscopy RAPID with a ×0.63 objective.…”
Section: Methodsmentioning
confidence: 99%